Impact of Bacterial Siderophores on Iron Status and Ionome in Pea - Lurthy, Tristan; Cantat, Cécile; Jeudy, Christian; Declerck, Philippe; Gallardo, Karine; Barraud, Catherine; Leroy, Fanny; Ourry, Alain; Lemanceau, Philippe; Salon, Christophe; Mazurier, Sylvie (Frontiers in Plant Science, 2020)
Including more grain legumes in cropping systems is important for the development of agroecological practices and the diversification of protein sources for human and animal consumption. Grain legume yield and quality is impacted by abiotic stresses resulting from fluctuating availabilities in essential nutrients such as iron deficiency chlorosis (IDC). Promoting plant iron nutrition could mitigate IDC that currently impedes legume cultivation in calcareous soils, and increase the iron content of legume seeds and its bioavailability. There is growing evidence that plant microbiota contribute to plant iron nutrition and might account for variations in the sensitivity of pea cultivars to iron deficiency and in fine to seed nutritional quality. Pyoverdine (pvd) siderophores synthesized by pseudomonads have been shown to promote iron nutrition in various plant species (Arabidopsis, clover and grasses). This study aimed to investigate the impact of three distinct ferripyoverdines (Fe-pvds) on iron status and the ionome of two pea cultivars (cv.) differing in their tolerance to IDC, (cv. S) being susceptible and (cv. T) tolerant. One pvd came from a pseudomonad strain isolated from the rhizosphere of cv. T (pvd1T), one from cv. S (pvd2S), and the third from a reference strain C7R12 (pvdC7R12). The results indicated that Fe-pvds differently impacted pea iron status and ionome, and that this impact varied both according to the pvd and the cultivar. Plant iron concentration was more increased by Fe-pvds in cv. T than in cv. S. Iron allocation within the plant was impacted by Fe-pvds in cv. T. Furthermore, Fe-pvds had the greatest favorable impact on iron nutrition in the cultivar from which the producing strain originated. This study evidences the impact of bacterial siderophores on pea iron status and pea ionome composition, and shows that this impact varies with the siderophore and host-plant cultivar, thereby emphasizing the specificity of these plant-microorganisms interactions. Our results support the possible contribution of pyoverdine-producing pseudomonads to differences in tolerance to IDC between pea cultivars. Indeed, the tolerant cv. T, as compared to the susceptible cv. S, benefited from bacterial siderophores for its iron nutrition to a greater extent.